Rice-common bean rotation under sprinkler irrigation effects of row spacing, fertilizer and cultivar on common bean yield and nutrient uptake - Stone, Luis Fernado; Pereira, Ana Lúcia (Pesquisa Agropecuaria Brasileira, 1994)
Effect of row spacings (30, 40, and 50 cm), fertilizer levels (300 and 500 kg/ha of formula 4-30-16), and cultivars (EMGOPA 201-Ouro, Carioca, TC 1558-1, and Mineiro Precoce), and the residual effect of previous rice (Oryza sativa L.) crop fertilization (250, 400, and 500 kg/ha of 4-30-16) were studied, during three years, on the grain yield and nutrient uptake of common bean (Phaseolus vulgaris L.) planted in rotation with rice under center pivot. For 'Carioca', 60 cm row spacing was used instead of 30 cm. 'Mineiro Precoce' and 'TC 1558-1' were replaced by 'RH 7-23' and 'Safira', from the second year onwards. Increasing bean fertilization increased grain yield of 'Mineiro Precoce', 'RH 7-23', and 'Safira'. At the lowest fertilizer level, the best grain yields were obtained with row spacing around 40 cm, except for 'TC 1558-1' and 'RH 7-23', in which 50 cm 'was more adequate. At the highest level, the adequate row spacing for 'Safira', 'TC 1558-1' and 'Carioca' were 30, 40 and 60 cm, respectively. The previous rice crop fertilization affected grain yield of the cultivars TC 1558-1 and Mineiro Precoce. Higher nutrient uptake occurred with higher fertilization and smaller row spacings.